2014
DOI: 10.1007/s11695-014-1374-z
|View full text |Cite|
|
Sign up to set email alerts
|

Buttressing the Staple Line: A Randomized Comparison Between Staple-Line Reinforcement Versus No Reinforcement During Sleeve Gastrectomy

Abstract: Bariatric surgery is recommended for Indian patients with body mass index (BMI) >32.5 kg/m2 with at least one comorbidity and >37.5 kg/m2 without a comorbidity. In laparoscopic sleeve gastrectomy, bleeding and leakage from the staple line are common post-operative events. Peri-Strips Dry® with Veritas® (PSD-V) is used in staple-line reinforcement. This was a single-investigator, multicenter, randomized study of 100 patients undergoing standard sleeve gastrectomy with a 34 or 36 French bougie. Patients were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 19 publications
0
26
1
2
Order By: Relevance
“…Our review of the literature identified 4 papers [1215], only 3 of which evaluated oversewing as a method of reinforcement [1315]. We included 3 additional papers [1618] not identified in our PubMed search.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review of the literature identified 4 papers [1215], only 3 of which evaluated oversewing as a method of reinforcement [1315]. We included 3 additional papers [1618] not identified in our PubMed search.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is sample bias in most studies of staple-line reinforcement. Because a sample size of > 1000 patients would be needed to reach statistical significance for postoperative bleeding and gastric leaks [12], the studies are unable to detect the differences between analyzed groups because of low power [1318]. …”
Section: Discussionmentioning
confidence: 99%
“…Berger et al [39] compared suture with 2 buttressing pledgets and did not find any differences in terms of bleeding. Shashank et al [40] reported that reinforcement of the line produces more leaks, but they did not note any differences in terms of bleeding. Wanjura et al [41] reported decreased bleeding with the addition of sutures, compared with no sutures.…”
Section: Discussionmentioning
confidence: 93%
“…In a randomized comparison, Shah et al found no significant difference in the leak rates in their set of patients. In the subset of patients with BMI < 43 they found increased bleeding risk from the staple line in the group where it was not reinforced as compared to those where PSD (Peri-strips dry) were used [ 11 ]. In a review by Chen et al, the authors comment that there is no reason to believe that the reinforcement leads to the reduction in the rate of staple line leak or bleeding [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that there are a large number of studies assessing various methods of making the staple line secure, there is till date no consensus on which technique is best for reducing the risk of leak. These intra-operative techniques include over-sewing the staple line, using absorbable or non-absorbable suturing material, omental wrap, and fibrin glues and so forth [ 11 ].…”
Section: Introductionmentioning
confidence: 99%